Bronchial Carcinoid Tumors with Massive Osseous Metaplasia: A Case Report and Review of the Literature - Mine ÖZŞEN; Ulviye YALÇINKAYA; Elif Ülker AKYILDIZ; Ahmet Sami BAYRAM; Gökhan GÖKALP (Federation of Turkish Pathology Societies, 2020)
Bronchial carcinoid tumors are primary lung neoplasms thought to originate from neuroendocrine cells, i.e. Kulchitsky cells, in the bronchial mucosa, although the type of cellular origin has not been clearly understood. A 61-year-old male patient underwent surgery and microscopic examination of the specimen revealed an anastomosing trabecular bony structure among the nests of tumor cells with round nucleus, granular chromatin, and large eosinophilic cytoplasm. Our case has been deemed worthy of being presented as bronchial carcinoid tumor with exaggerated osseous metaplasia.